2016
DOI: 10.1007/s11136-016-1272-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceived quality of life, 6 months after detoxification: Is abstinence a modifying factor?

Abstract: PurposePatients with a substance use disorder (SUD), admitted for detoxification, often suffer from a poor quality of life (QoL). We set out to monitor QoL, together with substance use, in a departure from the usual norm of measuring substance use alone as a treatment outcome. Literature searches revealed scant knowledge of how QoL is influenced. With this in mind, we aimed to investigate whether total abstinence, prior to follow-up, could influence QoL.MethodsWe studied a prospective cohort of 140 patients ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 37 publications
2
22
1
3
Order By: Relevance
“…Abstinence from substance use was experienced as crucial in recovery by some persons. In recent studies, abstinence from substance use has been associated with increased quality of life (Vederhus, Birkeland, & Clausen, 2016) and flourishing (McGaffin, Deane, Kelly, & Ciarrochi, 2015). Others described how they used substances as a way of managing everyday life, which is in line with a study of self-reported reasons for substance use in persons with severe mental illness (Pettersen, Ruud, Ravndal, & Landheim, 2013).…”
Section: Discussionmentioning
confidence: 57%
“…Abstinence from substance use was experienced as crucial in recovery by some persons. In recent studies, abstinence from substance use has been associated with increased quality of life (Vederhus, Birkeland, & Clausen, 2016) and flourishing (McGaffin, Deane, Kelly, & Ciarrochi, 2015). Others described how they used substances as a way of managing everyday life, which is in line with a study of self-reported reasons for substance use in persons with severe mental illness (Pettersen, Ruud, Ravndal, & Landheim, 2013).…”
Section: Discussionmentioning
confidence: 57%
“…Psychological distress (SCL-10) was the strongest variable explaining variations in QoL. A one-point gain (higher psychological distress) resulted in a 0.16 lower QoL-5 score in the final adjusted model, suggesting a substantial influence when applying the clinical interpretation of the scale [ 46 ]. The fit of the model was also strengthened considerably, and the explained variance in QoL increased from 33% to 56% with inclusion of this clinical variable.…”
Section: Discussionmentioning
confidence: 99%
“…QoL was measured with the QoL-5 [ 45 ], a generic, validated instrument covering overall QoL, based on an integrative theory of QoL and considered relevant as a disease-nonspecific instrument [ 45 47 ]. The reason for choosing the QoL questionnaire was that the instrument has been described as useful for measuring the overall QoL for both general population samples and across different illness domains [ 45 , 46 , 48 ]. It consists of five subjective QoL statements: two questions on mental and physical health, two questions on the quality of the relationship with important others (partner and friends), and one question regarding existential QoL, meaning relation to self.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we did not put a main focus on the changes within the SUD sample, a more detailed analysis of these changes has been published elsewhere. 36 Instead we compared the QoL of the two groups and controlled for the variables the two studies had in common in order to identify potential modifiable factors and increase the understanding of underlying mechanisms influencing QoL. The interventions in the SUD study (motivational intervention or brief advice about using MHGs after discharge) did not affect the patients’ QoL.…”
Section: Discussionmentioning
confidence: 99%